Characteristics and Surgical Results of Patients with Hypertrophic Obstructive Cardiomyopathy without Intrinsic Mitral Valve Diseases Undergoing Mitral Subvalvular Procedures during Myectomy - Qiang Ji; YuLin Wang; Ye Yang; LiMin Xia; WenJun Ding; Kai Song; ChunSheng Wang (Cardiology Research and Practice)
Background. Mitral subvalvular procedures have acquired a major role during hypertrophic obstructive cardiomyopathy (HOCM) surgery. However, few studies have focused on characterizing the clinical feature of HOCM patients without intrinsic mitral valve (MV) diseases undergoing mitral subvalvular procedures in addition to myectomy. Additionally, scant data about the results of mitral subvalvular procedures during HOCM surgery are available. This single-center study aims to characterize the clinical feature and surgical results of HOCM patients without intrinsic MV diseases undergoing mitral subvalvular procedures in addition to myectomy in comparison with those receiving myectomy alone. Methods. Among 181 eligible patients, 50 (27.6%) patients undergoing myectomy plus mitral subvalvular procedures were entered into the combined group, and the remaining 131 patients receiving myectomy alone were included in the alone group. Baseline and surgical characteristics were investigated, and surgical results were compared. Results. Comparatively, the combined group was younger (52.9 ± 11.2 years vs. 56.8 ± 11.8 years, p=0.045) and had a better New York Heart Association (NYHA) class (p=0.034) and less septal hypertrophy (16.4 ± 2.3 mm vs. 18.5 ± 3.2 mm, p<0.001). Septal thickness was independently associated with combined procedures in multivariable logistic regression analysis (OR = 0.887, 95% CI 0.612–0.917). No surgical death or iatrogenic septal perforation occurred in the combined group. Two (6.5%) patients in the combined group developed complete atrioventricular block and required permanent pacemaker implantation. During a median follow-up of 10 months, no deaths or reoperations were observed with the symptom of relief and NYHA class I or II in either group. Patients in the combined group as compared to the alone group had lower outflow tract gradients and a lower incidence of residual systolic anterior motion (SAM) syndrome. Conclusions. For HOCM patients without intrinsic MV diseases who are scheduled for surgery, a less pronounced septal hypertrophy may be closely associated with myectomy with concomitant mitral subvalvular procedures instead of myectomy alone. Mitral subvalvular procedures during myectomy are safe and allow the reduction of outflow tract gradients and freedom from SAM more effectively in comparison with myectomy alone.